Monitoring Mechanisms And Task Participation: The Mediating Effect Of Personal Responsibility - Lubogoyi, Bumaali; Kasekende, Francis; Ngoma, Muhammed; John , C. Munene (Universiti Sains Malaysia, 2016)

(untitled)
This study investigates the mediating role of personal responsibility on the link between monitoring mechanisms and task participation. Design/methodology/approach – The proposed hypotheses were tested on a sample of local government employees in Uganda. Using Analysis of Moment Structures (AMOS), research from the monitoring mechanisms, personal responsibility and task participation literatures was analyzed and integrated to put forth a new theoretical lens, represented by the structural equation model developed in this paper that helps to explain local governments’ employee task participation. Findings – Development of the model reveals a relationship between monitoring mechanisms, personal responsibility and task participation among local government employees. This model also highlights the importance of personal responsibility in mediating the relationship between monitoring mechanisms and task participation. Originality/value – The study findings enrich organizational behavior studies by confirming that monitoring mechanisms and personal responsibility are key antecedents of task participation. Secondly, the study is one of the pioneers to demonstrate that the presence of personal responsibility helps to extend the positive effects monitoring mechanisms have on task participation.